Mapping the receptivity of malaria risk to plan the future of control in Somalia - Noor, A; Alegana, V; Patil, A; Moloney, G; Borle, M; Yusuf, F; Amran, J; Snow, R (BMJ Publishing Group, 2012)
OBJECTIVES: To measure the receptive risks of malaria in Somalia and compare decisions on intervention scale-up based on this map and the more widely used contemporary risk maps. DESIGN: Cross-sectional community Plasmodium falciparum parasite rate (PfPR) data for the period 2007-2010 corrected to a standard age range of 2 to <10 years (PfPR(2-10)) and used within a Bayesian space-time geostatistical framework to predict the contemporary (2010) mean PfPR(2-10) and the maximum annual mean PfPR(2-10) (receptive) from the highest predicted PfPR(2-10) value over the study period as an estimate of receptivity. SETTING: Randomly sampled communities in Somalia. PARTICIPANTS: Randomly sampled individuals of all ages. MAIN OUTCOME MEASURE: Cartographic descriptions of malaria receptivity and contemporary risks in Somalia at the district level. RESULTS: The contemporary annual PfPR(2-10) map estimated that all districts (n=74) and population (n=8.4 million) in Somalia were under hypoendemic transmission (≤10% PfPR(2-10)). Of these, 23% of the districts, home to 13% of the population, were under transmission of <1% PfPR(2-10). About 58% of the districts and 55% of the population were in the risk class of 1% to <5% PfPR(2-10). In contrast, the receptivity map estimated 65% of the districts and 69% of the population were under mesoendemic transmission (>10%-50% PfPR(2-10)) and the rest as hypoendemic. CONCLUSION: Compared with maps of receptive risks, contemporary maps of transmission mask disparities of malaria risk necessary to prioritise and sustain future control. As malaria risk declines across Africa, efforts must be invested in measuring receptivity for efficient control planning.